BARRIERS TO POLITICAL PARTICIPATION FOR WOMEN IN INDIA - Ajay kumar (International Journal of Multidisciplinary Research and Studies, 2021)
The concept of development may also be used to refer to an action. This is due to the fact that any activity that contributes to growth must involve some kind of action; without action, development cannot take place. The word "development," on the other hand, can be understood in a number of different ways by a number of different people depending on the context in which it is used. For instance, the requirements for a populace that is starving must be very different from those of a population that receives an adequate amount of nutrients It is important to point out that "economic growth as measured solely in terms of annual increases in pre-capita income or gross national product, regardless of its distribution and the degree to which people's participation in effective growth" is not the same thing as "development," despite the fact that the two concepts are frequently confused with one another (Mahmoud, 1991). Regarding this topic, we might also consider the viewpoint presented by Pearson (1992). His understanding of development is that it entails "An improvement qualitative, quantitative, or both - in the utilisation of existing resources.